Effect of Butea Superba. Roxb root extract on male hamster fertility - Tocharus, Chainarong; Shimbhu, Dawan; Tocharus, Jiraporn; Ruchiratanti-angkoor, Arampa (Biomedical Sciences and Clinical Medicine, 2024)
Objective To investigate the long term effects of ethanolic extracts of Butea superba Roxb. root on sperm number and fertility, sperm quality and histology of testis in male hamsters. Methods Male hamsters (100-120 g) were divided into four equal groups: one control group and three different treatment groups. The control group received distilled water orally each day for 6 months. The treatment groups were fed with alcoholic extract suspensions of B. superba root at doses of 0.1, 1 or 10 mg/kg BW/day for 6 months. The fertility of sperm was assessed by determining the number of 2-cell embryos collected from super-ovulated female hamsters after mating. The quality of sperm in male hamsters treated with B. superba was evaluated by counting the number of sperm, and the number of intact acrosomes on the sperm head. Histopathologic study of the testes was performed to evaluate the number of spematogonia. Results After six months of daily oral treatment with root extract, the sperm count was increased in the treated male hamsters in a dose-dependent manner. The number of 2-cell embryos in superovulated females, after mating with treated males, was significantly greater in B. superba-treated groups than in the control group. There was no change between the treated and control group in the percentage of sperm with acrosome. No pathology of reproductive organs was observed. Conclusion B. superba root extract increases spermatogenesis among male hamsters, without affecting fertility and acrosome integrity, after 6 months of oral treatment.